IDENTIFICATION AND BIOLOGICAL CONTROL OF BASAL STEM AND ROOT ROT DISEASE OF SNAPDRAGON - Nadeem Ramadan (Mesopotamia Journal of Agriculture)
For the first time wilt symptoms have been detected on the Snapdragon (Antirrhinum majus L) plants cultivated in the parks of Mosul University. The isolation of fungi from wilted plants on PDA medium revealed the presence of seven genera including; Alternaria, Aspergillus, Cladosporium, Fusarium, Macrophomina, Penicillium and Stemphyllium. Fusarium oxysporum was the most frequent fungi approached 36.0 x 102 Colony Forming Unit/gm soil. F.oxysporum reduced significantly the chlorophyll content of infected plants, and the percentage of its inhibition increased up to 81.88 in severe infections. The infection caused significance stunting of plants when plant height inhibited by 58.09% in dead plants. Antagonism ability of Trichoderma species as T.harzianum, T. viride, and T. reesei  against F. oxysporum showed control efficiency of.1.666, 2.333, and 2.666 respectively.